2020
DOI: 10.1088/1748-9326/ab6c70
|View full text |Cite
|
Sign up to set email alerts
|

Wildland fire reburning trends across the US West suggest only short-term negative feedback and differing climatic effects

Abstract: Wildfires are a significant agent of disturbance in forests and highly sensitive to climate change. Short-interval fires and high severity (mortality-causing) fires in particular, may catalyze rapid and substantial ecosystem shifts by eliminating woody species and triggering conversions from forest to shrub or grassland ecosystems. Modeling and fine-scale observations suggest negative feedbacks between fire and fuels should limit reburn prevalence as overall fire frequency rises. However, while we have good in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 40 publications
3
43
0
Order By: Relevance
“…For example, the long-term impact of repeated fires on vegetation and fuels is not well understood across biophysical gradients, and will be conditional on factors such as tree mortality following the initial or second fire, exact time interval between fires, postfire climate, and dominant species (McKenzie and Littell 2017 , Hurteau et al 2019a ). Fortunately, quantifying ecosystem responses to short-interval fires is an extremely active area of research that is filling knowledge gaps (Coop et al 2016 , Coppelletta et al 2016, Harvey et al 2016a , Tepley et al 2017 , Collins et al 2018 , Parks et al 2018b , Lydersen et al 2019 , Turner et al 2019 , Whitman et al 2019 , Buma et al 2020 ).…”
Section: What Does the Future Hold For Western North American Forestsmentioning
confidence: 99%
“…For example, the long-term impact of repeated fires on vegetation and fuels is not well understood across biophysical gradients, and will be conditional on factors such as tree mortality following the initial or second fire, exact time interval between fires, postfire climate, and dominant species (McKenzie and Littell 2017 , Hurteau et al 2019a ). Fortunately, quantifying ecosystem responses to short-interval fires is an extremely active area of research that is filling knowledge gaps (Coop et al 2016 , Coppelletta et al 2016, Harvey et al 2016a , Tepley et al 2017 , Collins et al 2018 , Parks et al 2018b , Lydersen et al 2019 , Turner et al 2019 , Whitman et al 2019 , Buma et al 2020 ).…”
Section: What Does the Future Hold For Western North American Forestsmentioning
confidence: 99%
“…This limits our understanding of the ongoing effects of continued short‐interval disturbances. While modeling suggests progressive loss in ecosystem functions (e.g., ongoing fires in Yellowstone, Westerling et al 2011), it is also true that subsequent disturbances interact with previous disturbance conditions, changing severity and overall impacts which can limit future disturbance severity or even occurrence (Parks et al 2015, Buma et al 2020). Trajectories inferred from single short‐interval events may therefore not be valid if frequency of disturbances remains high.…”
Section: Introductionmentioning
confidence: 99%
“…The definition of short‐interval fires varies by study (e.g., 5 or 25 yr, Buma et al 2020, Fairman et al 2019; 50 yr, McRae et al 2006, 30 yr, Turner et al 2019), but for the boreal forest can be functionally defined as when second (or third) fires occur prior to the time required to regenerate the local serotinous seedbanks, extirpating local populations and facilitating rapid forest type conversion (Buma et al 2013, Enright 2015). Here we investigate fire return intervals from 12 to 30 yr (see Methods ; Appendix : Table S1) and define short‐interval fires for discussion purposes within this region as <50 yr given system‐specific research that suggests 50 yr or more are required for full aerial seedbank regeneration (Johnstone et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Observed and projected increases in both global forest fire activity (Andela et al, 2017) and reburns in western US forests (Buma et al, 2020) highlight the need to better understand the top-down and bottom-up controls on refugia occurrence and persistence. We found that pattern-process relationships shift in relative importance as landscapes pass through successive fire filters, and repeat burning appears to amplify the effect of terrain features.…”
Section: Con Clus Ionmentioning
confidence: 99%
“…Wildfire‐driven conversions of forest to alternative states can occur when high‐severity fire overwhelms species’ fire‐adaptive traits at local and landscape scales (Johnstone et al, 2016 ; Whitman et al, 2019 ). In some cases, repeat burning, also referred to as “reburn” or “short‐interval fire” (Buma et al, 2020 ; Prichard et al, 2017 ), can result in forest loss when species’ resistance (ability to remain relatively unchanged by fire) and resilience (ability to recover following fire) mechanisms are overwhelmed (Bowman et al, 2014 ; Holz et al, 2015 ; Turner et al, 2019 ). In contrast, some places persist as forest when surrounding areas burn at higher frequency and/or severity, and these “fire refugia” are important features of landscapes where high‐severity reburn is increasing (Collins et al, 2019 ; Coop et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%